Large-scale farming operations are win-win for grain production, soil carbon storage and mitigation of greenhouse gases. (20th January 2018) - Zhu, Yongchang; Waqas, Muhammad Ahmed; Li, Yu'e; Zou, Xiaoxia; Jiang, Defeng; Wilkes, Andreas; Qin, Xiaobo; Gao, Qingzhu; Wan, Yunfan; Hasbagan, Ganjurjav
Abstract: Scaling up of farming operations by land use rights transfers has been a growing trend in China in recent years. However, little is known about the implications of this trend for greenhouse gas (GHG) emissions and soil organic carbon (SOC) stock changes. Using farm survey data from Shandong Province, a typical grain production region in China, we used a life cycle assessment (LCA) method to evaluate the impact of different farm scales on input use efficiency, grain production, SOC stock changes and GHG emissions. Large-scale farming operations (LSFO) enhanced input use efficiency by reducing fertilizer and pesticide consumption rates and energy use for irrigation. Compared with small household farming operations (SHFO), LSFO attained higher grain yield in wheat-maize and wheat-rice cropping systems. Compared with small farms, carbon footprints per unit area of large-scale farms were lower for wheat (17%) and maize (28%) in the wheat-maize cropping system and for wheat (14%) and rice (8%) in the wheat-rice cropping system. Moreover, LSFO reduced GHG emissions (7–21%) and enhanced SOC stocks (6–9%), compared with SHFO. This study highlights that in China, land use rights transfers to promote large-scale farming can help achieve cleaner grain production with less negative impact on the environment. Highlights: Large-scale operators achieved higher resource use efficiency and lower carbon footprints compared to small households. Large-scale farming operations increased SOC stocks and system productivity in wheat-maize and wheat-rice rotation systems. Land use transfer and avoiding rice planting in water scarce area can help to gain cleaner production.